Vertical distribution and transformation of phosphorus and iron in paddy soils during the whole growth stage of rice - Li, Yun; Chen, Minghong; Liu, Xuanye (Frontiers in Earth Science, 2022)
Due to the different water requirements of rice at different growth stages, paddy fields present special water and soil environments with alternating wet and dry conditions throughout the growth stage, thus affecting the hydrological cycle and phosphorus transformation and transport processes in paddy fields. In this study, we selected a test field in Heping Irrigation District, Suihua, Heilongjiang Province, China, and used in-situ field measurements to determine the vertical distribution of dissolved oxygen (DO)-phosphorus (P)-iron (Fe) concentrations and the corresponding hydrological environment and meteorological data of the paddy field during the whole growth stage, respectively. The measured results showed strong correlations between vertical DO, DGT-labile P and Fe concentrations, and soluble P and Fe concentrations in pore water in paddy soils. Changes in the hydrological environment of the paddy field during different growth stages led to changes in soil vertical DO concentrations and, consequently, vertical soil P and Fe concentrations. Soil DO concentrations in the paddy field were smaller during the tillering, booting, and heading to flowering stages. At the same time, soluble P fluxes released through soil-water interface (SWI) overlying water were more significant in these three stages. At the same time, the soils of these three growth stages also have a large P buffering capacity and potential for sustained P release. Therefore, water management in paddy fields requires special attention to the hydrological environment during these three reproductive periods to reduce the possible release of soil P. Our results can provide an essential reference for the transformation and control of soil P and Fe in paddy fields during the whole growth stage of rice.